Bioimpedance vector analysis-derived body composition influences strength and power in alpine skiers - Bertozzi, F.; Tenderini, D.; Camuncoli, F.; Simoni, G.; Galli, M.; Tarabini, M. (Research Quarterly for Exercise and Sport, 2024)
Purpose Alpine ski racing is a complex sport where no single factor can exclusively account for performance. We assessed body composition, using bioelectrical impedance vector analysis (BIVA), and our purpose was to study its influence on the strength and power profile of young alpine skiers.